2022
DOI: 10.1186/s12913-022-08319-1
|View full text |Cite
|
Sign up to set email alerts
|

Determinants of accident and emergency attendances and emergency admissions in infants: birth cohort study

Abstract: Background There is limited understanding of the drivers of increasing infant accident and emergency (A&E) attendances and emergency hospital admissions across England. We examine variations in use of emergency hospital services among infants by local areas in England and investigate the extent to which infant and socio-economic factors explain these variations. Methods Birth cohort study using linked administrative Hospital Episode Statistics … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2
2

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 52 publications
0
2
0
Order By: Relevance
“…We also selected the following variables to be summarised given their association with migration and/or hospital admission rates as shown in the research literature: maternal self-reported ethnicity, child’s sex, region of residence, presence of congenital anomaly, year of birth and maternal age (see Supplementary Table 2 for definitions). 1,17,21,22 To help guide the selection of confounders for our final statistical models, we constructed a directed acyclic graph (DAG) of variables that are related to parental migration and child hospital admissions. Supplementary Figure 1 shows a simplified DAG of maternal country of birth and child emergency admissions.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…We also selected the following variables to be summarised given their association with migration and/or hospital admission rates as shown in the research literature: maternal self-reported ethnicity, child’s sex, region of residence, presence of congenital anomaly, year of birth and maternal age (see Supplementary Table 2 for definitions). 1,17,21,22 To help guide the selection of confounders for our final statistical models, we constructed a directed acyclic graph (DAG) of variables that are related to parental migration and child hospital admissions. Supplementary Figure 1 shows a simplified DAG of maternal country of birth and child emergency admissions.…”
Section: Methodsmentioning
confidence: 99%
“…We repeated the above analyses stratifying the cohort by London or non-London region of birth to account for known geographical variability in migrant populations and incidence rates of hospital admissions, particularly in differential thresholds for admissions. 21 Secondly, since data on embarkations from the UK were not available and very few emigrations are captured in HES, we ran simulations to assess how different levels of international emigration could affect the final results (see Appendix C for details).…”
Section: Methodsmentioning
confidence: 99%